Short- and long-term efficacy of endoscopic balloon dilation in Crohn’s disease strictures - de’Angelis, Nicola (Baishideng Publishing Group Co., Limited, 2013)
AIM: To evaluate short- and long-term efficacy of endoscopic balloon dilation in a cohort of consecutive patients with symptomatic Crohn’s disease (CD)-related strictures. METHODS: Twenty-six CD patients (11 men; median age 36.8 year, range 11-65 years) with 27 symptomatic strictures underwent endoscopic balloon dilation (EBD). Both naive and post-operative strictures, of any length and diameter, with or without associated fistula were included. After a clinical and radiological assessment, EBD was performed with a Microvasive Rigiflex through the scope balloon system. The procedure was considered successful if no symptom reoccurred in the following 6 mo. The long-term clinical outcome was to avoid surgery. RESULTS: The mean follow-up time was 40.7 ± 5.7 mo (range 10-94 mo). In this period, forty-six EBD were performed with a technical success of 100%. No procedure-related complication was reported. Surgery was avoided in 92.6% of the patients during the entire follow-up. Two patients, both presenting ileocecal strictures associated with fistula, failed to respond to the treatment and underwent surgical strictures resection. Of the 24 patients who did not undergo surgery, 11 patients received 1 EBD, and 13 required further dilations over time for the treatment of relapsing strictures (7 patients underwent 2 dilations, 5 patients 3 dilations, and 1 patient 4 dilations). Overall, the EBD success rate after the first dilation was 81.5%. No difference was observed between the EBD success rate for naive (n = 12) and post-operative (n = 15) CD related strictures (P > 0.05). CONCLUSION: EBD appears to be a safe and effective procedure in the therapeutic management of CD-related strictures of any origin and dimension in order to prevent surgery.